SP6.1.4 Novel methods to enhance anti-tumour immunity in oesophageal adenocarcinoma; hypofractionated radiotherapy may be superior to CROSS regimen chemo-radiation. (9th August 2022) - Donlon, Noel; Davern, Maria; Sheppard, Andrew; Donohoe, Claire; Reynolds, John; Lysaght, Joanne
Abstract: Background: CROSS regimen (41.4Gy;carboplatin&paclitaxel) is a standard trim-modality treatment for locally advanced oesophageal adenocarcinoma (OAC). The addition of adjuvant immunotherapy targeting PD-L1 may improve outcomes, hence the impact of radiation therapy on the tumour microenvironment is of considerable interest. The dosing has not been studied in this context, especially hypofractionation, and this study explored immunogenic cell death, specifically Damage Associated Molecular Pattern (DAMPs) release, and the impact of immune checkpoint blockade(ICB). Methods: The ability of CROSS-regimen (3×1.8Gy) and hypo-fractionation (3×4Gy) to induce immunogenic cell death was assessed by flow cytometry of DAMPs calreticulin&HMGB-1.Expression of DAMPs were evaluated on OAC tumour and whole blood samples (n=10) pre and post conventional therapies versus hypofractionation. The immunostimulatory effect of CROSS and hypofractionation using post-treatment tumour cell secretomes with/without ICB on the cytolytic ability of OAC-donor lymphocytes was interrogated by CCK8-assay. Results: The expression of Calreticulin&HMGB1 was significantly higher on tumour tissue compared to whole blood post chemo(radio)therapy(p<0.01). Hypofractionation increased TNF-α&IFN-γ production by T-cells greater than CROSS fractions ex vivo(p<0.01). The post-CROSS and hyporfractionated tumour cell secretome enhanced lymphocyte mediated killing of tumour cells(p<0.01), further enhanced with dual immune checkpoint blockade (nivolumab&ipilimumab)(p<0.01). High expressors of DAMPs pre-operatively had a significantly (P<0.01) better Tumour Regression Grade (TRG1–2) compared to low expressors. Conclusions: The current CROSS regimen radiation for OAC is immunogenic, however, hypo-fractionated doses boosted the immune response to OAC, and was synergistic with ICB. This may warrant further exploration in a clinical and translational trial.